Changing the conductivity of porous silicon with silver nanoparticles/silicon structures when detecting hydrogen peroxide - Kutova, O. Yu.; Dusheiko, M. G.; Loboda, B. O.; Obukhova, Т. Ю. (Technology and design in electronic equipment, 2018)
The authors investigate the influence of hydrogen peroxide concentration on the conductivity of the porous silicon with silver nanoparticles / crystalline silicon system. A simple resistive sensor with Ag nanoparticles was used as a catalyst in order to study processes occuring in porous silicon during hydrogen peroxide detection. Porous silicon was formed using a two-stage metal-assisted chemical etching with Ag nanoparticles. It was shown that two simultaneous processes are involved here: carrier extraction to porous silicon caused by interaction with hydrogen peroxide molecules and heating caused by hydrogen peroxide decomposition in presence of Ag nanoparticles. Dimensions of the investigated sensor structure were comparable with a drop of the solution, thus at 30‰ concentration heating could reach 10°C. As porous silicon/crystalline silicon system has a negative temperature coefficient, two above mentioned processes counteract which leads to a maximum, or saturation, on the graph of the dependence of resistivity on hydrogen peroxide concentration at 10—11‰. Sensitivity declines from 0.001—0.02 to 0.0001—0.0003%/‰. To prove these thesis resistivity-concentration dependences were adjusted taking into account calculated heating caused by hydrogen peroxide decomposition. It was shown that in this case the slope of the dependence curve remains stable up to 30‰ and sensitivity remains about 0.001—0.02%/‰.